Implementasi Program Laskar Nagari Peduli Pangan dan Gizi (LNPPG) dalam Pencegahan Stunting di Kabupaten Padang Pariaman - Atika Yasri; Ramadhani Yusran (Policy, Law and Political Research Center, 2022)
This research was conducted in Padang Pariaman Regency wit theaimofdescribing the implementationof the Laskar Nagari Program for Food and Nutrition Care (LNPPG) in the Prevention of Stunting. Thisstudy uses qualitativeapproach withdescriptivemethods. The research location is in the Padang Pariaman Regency. The research informants were determined by purposive sampling. Data collection techniques are carried out through interviews, observations, and documentation studies and data reduction is carried out so that accurate conclusions can be drawn from the data that has been obtained. The results of this study prove that the implementation of the LNPPG Program in Stunting Prevention is carried out in the form of counseling from the health department to the community, establishing health posts, providing additional food. However, the implementation is still experiencing various obstacles so that it has not been able to achieve the expected goals. For example, the level of community participation is low, this is due to the difficulty of the community understanding the importance of this program, the low consistency of cadres / implementers in doing their work, the credibility / quality of cadres / implementors is not all good even though there are guidance and training, and the minimum budget available and inadequate facilities, aswellasthedifficulty of accessing the location and the terrain that is difficult to pass when conducting this LNPPG program extension. This problem has resulted in the LNPPG Program's achievements not being optimally realized.